Teoría democrática deliberativa y ciencia política empírica = Democratic Theory and Empirical Political Science (2017)
I examine three different ways in which the ideals of deliberative democracy have changed in the light of practical concerns about its viability. have changed in the light of practical concerns about its viability, i.e., making increasingly important the problem of how this ideal can approach societies characterized by deep disagreements, social problems of enormous complexity and inoperative instruments in their existing institutions. (1) Theories of deliberative democracy emphasize the process of deliberation rather than its ideal conditions and procedures. (2) Deliberative democrats are increasingly interested in the problems of institutionalization, in making voting, majority rule and representation more deliberative institutions. (3) Deliberativists examine the different scenarios and procedures of deliberation, pointing out obstacles that cannot always be anticipated by resorting only to conceptual arguments